WOMEN OFFICERS, OFFICER LIKE QUALITIES (OLQS) AND ETHOS OF THE INDIAN ARMED FORCES (International Journal of Engineering Sciences & Management Research, 2018)
Serving in Indian Armed Forces as an Officer is an apparent responsibility followed by the challenging scenarios both for men and women. Customarily in Indian Armed Forces, to be an Officer one must possess the Officer Like Qualities (OLQs) and ironically it is believed that such kinds of qualities are present in everyone but responsiveness may deviate from person to person. Comprehensively the surrounding environment, its influence and individual thinking; together all develop a person as he or she is and with multi faceted service like Indian Armed Forces, it becomes certain to have some special skills like Honesty, Integrity, Leadership, Physical Fitness and Psychology with various intensities. This paper provides detailed suggestions for developing dynamic Officer Like Qualities in future officers, men and women. The paramount target of this paper is young scholars having desire to join Indian Armed Forces; however authors with all level of proficiency may find useful intellection in the paper.